The Most Effective Methods Used by Advanced Countries in the Fight against COVID – 19 and their Successes (LIS TODAY, 2021)
COVID-19 has been spreading and killing hundreds of thousands of people worldwide thereby  necessitating measures are required that will drastically reduce the spread of the pandemic. The  preliminary investigation of the researchers concretized the reality that Corona virus is yet to have a  cure or endorsed vaccine from the World Health Organization (WHO) – a bird’s eye view possibility  in measuring the pandemic response success. The option left therefore, is to take precaution in  curtailing the further spread through behavioral measures – namely; keeping a safe distance,  avoiding social gatherings, washing hands, and reducing social contact and also, treating the noticed  symptoms speedily. Although these measures are universal, advanced countries have evolved better  approaches in prevention and control of the spread through the use of artificial intelligence (AI), big  data, cloud computing, block chain and 5G, which have effectively improved the efficiency of the  countries’ efforts in epidemic monitoring, virus tracking, prevention, control and treatment, and  resource allocation. This research therefore draws the methods used in those advanced countries in  contrast to those of developing or developed countries in fighting against the pandemic while  considering recorded successes that will serve as a guide for pandemic response and preparedness  plans.
Keywords: Most effective methods; Advanced Countries; COVID-19; Successes; Pandemic Preparedness Plan